Breadth, polarity, and emergence of character strengths and their relevance for assessment. Issue 3 (4th May 2023) - Arbenz, Gian Carlo; Gander, Fabian; Ruch, Willibald
ABSTRACT: Research activity on correlates of character strengths has been steadily increasing in the past years. However, very little is known about basic properties of character strengths, such as their conceptual breadth (narrow versus broader strengths), polarity (unipolar versus bipolar strengths), and emergence (phasic versus tonic strengths). These properties are relevant to the operationalization of character strengths and likely also for related interventions. We therefore asked a sample of N = 249 psychologists to rate the breadth, polarity, and emergence of the 24 character strengths. The results provide a first account of these properties and suggest a considerable variety in them. Our analysis suggests that the content validity of the VIA-IS and VIA-IS-R may be limited as these variety was apparently not sufficiently accounted for in these instruments. We call for further research on such basic properties and propose that these findings are considered for the future assessment of character strengths.